Study of Variation of ACOX1 Gene Among Different Horse Breeds Maintained in Iran - Shayan Boozarjomehri Amnieh; Ali Hassanpour; Sina Moghaddam; Fatemeh Sakhaee; Katarzyna Ropka-Molik (Animals)
The ACOX1 gene is vital for fatty acid metabolism and is linked to environmental stress and physical exertion adaptation. The p.Asp237Ser variant (rs782885985) in ACOX1 is associated with increased enzyme activity and reactive oxygen species (ROS) levels. This study examined the ACOX1 polymorphism across six horse breeds in Iran: Arabian, Thoroughbred, KWPN, Caspian, Kurdish, and Turkmen. The goal was to identify differences in ACOX1 genotype distribution, potentially serving as genetic markers under selection pressure related to breed-specific traits. In a sample of 324 horses, genomic DNA was analyzed using PCR-RFLP, revealing three genotypes (TT, TG, GG). The GG genotype was most common in Kurdish and Arabian horses (86% and 70%, respectively), while the TT genotype was prevalent in Turkmen (24%) and Thoroughbred horses (23%). The T allele’s frequency in Thoroughbred and Turkmen horses suggests that ACOX1 may be under selection pressure for phenotypic traits. Differences in genotype distribution were confirmed among breeds, with no sex-based association. The study concludes that ACOX1 is a potential genetic marker for horse performance and adaptability, emphasizing the importance of genetic diversity in breeding programs.